Southeast Asian Independent Cinema - Baumgärtel, Tilman, 1966- (Book collections on Project MUSE., 2012)
The rise of independent cinema in Southeast Asia, following the emergence of a new generation of filmmakers there, is among the most significant recent developments in global cinema. This book documents these developments as a genuine outcome of the democratization and liberalization of film production.